(untitled) (The Pakistan Development Review, 2025)
Strangely “to go or not to go to the IMF” continues to dominate the economic debate in Pakistan. All manner of statements have come out of the economic leaders in the government and their advisers. “We don’t need to go to the IMF if we ban importing luxury items.” “We can borrow our way out of our problems for our problems are only current financing.” “With borrowing, IMF will reduce any conditions.” These statements merely show the lack of understanding of the role of the IMF. As always, government has relied on hurriedly put together committees where people float in and out to consider this existential question. But the answer remains elusive. So, let us clear the confusion.